Real Time Monitoring Small Scale Off Grid Solar System with Blynk App - Annamalar,; Ts. Mohd Fadly Bin Abd Razak, (Progress in Engineering Application and Technology, 2023)
This research project aims to address the need for a monitoring system specifically designed for small solar grid systems. With the increasing popularity of solar panels as a practical and environmentally friendly means of generating electricity, it is crucial to ensure the effective operation and maintenance of these systems, particularly in off-grid living areas. To achieve this objective, the project focuses on developing a user-friendly monitoring system utilizing the Arduino ESP32 microcontroller and the Blynk software. The Arduino ESP32 serves as the main controller, gathering real-time data from sensors and solar panels to evaluate system performance. Key factors such as battery levels, voltage, and current are continuously monitored to provide clients with valuable insights into their small-scale grid systems. The system employs optimized data collection methods and error management systems to ensure stability and reliability. The collected data is securely transmitted to the Blynk app, enabling users to remotely monitor their solar power installations in real-time. The Blynk software offers visual representations such as measurements and graphs, facilitating data interpretation and analysis. By identifying patterns and potential issues through this monitoring system, users can make informed decisions regarding the most effective utilization of their solar power systems. The project's overarching goal is to provide individuals with an accessible means of monitoring their solar power installations. By leveraging the Arduino ESP32 microcontroller and the user-friendly Blynk software, users can effectively manage their energy consumption and contribute to the development of sustainable energy systems.